2015
DOI: 10.3390/ijms160511689
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized LDL Is Strictly Limited to Hyperthyroidism Irrespective of Fat Feeding in Female Sprague Dawley Rats

Abstract: Metabolic dysfunctions might play a crucial role in the pathophysiology of thyroid dysfunctions. This study aimed to investigate the impact of a controlled diet (normal versus high fat feeding) on hypothyroid and hyperthyroid Sprague Dawley rats. Female Sprague Dawley rats (n = 66) were grouped into normal diet (n = 30) and high-fat diet (n = 36) groups and subdivided into controls, hypothyroid and hyperthyroid groups, induced through propylthiouracil or triiodothyronine (T3) treatment, respectively. After 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 25 publications
2
5
0
Order By: Relevance
“…*p < 0.05, **p < 0.01 compared to appropriate sedentary control group; # p < 0.05 compared to appropriate normal diet control group. £ p < 0.05, ££ p < 0.01, £££ p < 0.001 compared to baseline control group we obtained in young and old control animals are in line with a previous study in SD rats [11].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…*p < 0.05, **p < 0.01 compared to appropriate sedentary control group; # p < 0.05 compared to appropriate normal diet control group. £ p < 0.05, ££ p < 0.01, £££ p < 0.001 compared to baseline control group we obtained in young and old control animals are in line with a previous study in SD rats [11].…”
Section: Discussionsupporting
confidence: 93%
“…In our laboratory, all methods are strictly controlled by internal and external quality controls. Furthermore, the lipid concentrations that we obtained in young and old control animals are in line with a previous study in SD rats [ 11 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Previous studies have shown that thyroid dysfunction is accompanied by changes in caloric intake and body weight, as well as changes in the lipid profile. Hypothyroid rats showed significantly decreased oxidized LDL levels, whereas hyperthyroid rats showed significantly increased oxidized LDL levels ( 30 ). Another report showed that oxidized LDL levels in 125 obese human patients were positively correlated with body mass index and T-Cho concentration ( 31 ).…”
Section: Discussionmentioning
confidence: 99%